The clinicopathologic and immunohistochemical features of villoglandular adenocarcinoma of uterine cervix - Zhuo-Ya Huang; Sisi Zhang; Yao-Zhong Zhang; Jian-Hong An; Jiao Luo; Peng-Juan Liao; Qing Chen; Hong Shen (Wolters Kluwer Medknow Publications, 2018)
Aim: Villoglandular adenocarcinoma (VGA) of the uterine cervix is a variant of endocervical adenocarcinoma. However, the clinicopathologic and immunohistochemical features of VGA are still unclear. The aim of this study was to investigate the clinicopathologic and immunohistochemical features of VGA. Materials and Methods: A total of 20 VGA patients were identified among 852 patients diagnosed with cervical cancer and enrolled in this study. The immunohistochemical levels of Ki-67, P53, P16, progesterone receptor (PR), carcinoembryonic antigen (CEA), vimentin (Vim), and estrogen receptor (ER) were measured by immunohistochemistry. Results: VGA was prevalent in younger women and presented favorable prognosis. Ki-67, P16, and CEA were highly expressed in VGA tissues, while PR expression was hardly to be detected. The positive rates of Ki-67, CEA, and P16 were 90.0%, 90.0%, and 85.0%, respectively, which were significantly higher compared with PR (5.0%, P < 0.001). In addition, the positive rates of P53, Vim, and ER in VGA tissues were 55.0%, 50.0%, and 40.0%, respectively. However, the expression levels of Ki-67, P53, P16, PR, CEA, Vim, and ER were not significantly associated with clinical features (P > 0.05). Conclusion: These data indicate that VGA is a rare cervical adenocarcinoma, which is prevalent in younger women, and presents favorable prognosis. Detection of Ki-67, P53, P16, PR, CEA, Vim, and ER would be beneficial for the diagnosis of VGA.